Screening of wild deer populations for exposure to SARS‐CoV‐2 in the United Kingdom, 2020–2021. Issue 5 (8th April 2022) - Holding, Maya; Otter, Ashley David; Dowall, Stuart; Takumi, Katsuhisa; Hicks, Bethany; Coleman, Tom; Hemingway, Georgia; Royds, Matthew; Findlay‐Wilson, Stephen; Curran‐French, Mollie; Vipond, Richard; Sprong, Hein; et al.
Abstract: Following findings in Northern America of SARS‐CoV‐2 infections in white‐tailed deer, there is concern of similar infections in European deer and their potential as reservoirs of SARS‐CoV‐2 including opportunities for the emergence of new variants. UK deer sera were collected in 2020–2021 from 6 species and a hybrid with 1748 tested using anti‐spike and anti‐nucleocapsid serology assays. No samples were positive on both assays nor by surrogate neutralization testing. There is no evidence that spill‐over infections of SARS‐CoV‐2 occurred from the human population to UK deer or that SARS‐CoV‐2 has been circulating in UK deer (over the study period). Although it cannot be ruled out, study results indicate that spill‐over infections followed by circulation of SARS‐CoV‐2 to the most common European deer species is small.